(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
This paper introduces the turbine governor (TG) and automatic voltage regulator (AVR) and new Adaptive Neuro-Fuzzy Inference System (ANFIS) to search for improvement and the stability. MATLAB use on 3bus system and 3-phase faults between B1 and B2 systems with and without (TG), (AVR) and (ANFIS) at = 5 sec. and = 5.2 sec. From the results obtained from the simulations, conclude that the voltage is in a stable state whether the rotor angle is stable or unstable. (TG), (AVR) and (ANFIS) use in the grid have a role in the transient stability of the system and the voltage is improved.